Hydrolysis of Nitrile in Presence of Different Zeolite Catalysts Under Microwave IR-Radiation - Singh, Ravinder; Kumar, Ramesh (Asian Journal of Chemistry, 2011)
The hydrolysis of nitriles in presence of different zeolite catalysts under microwave irradiations gives corresponding amide in high yield in few minutes.